High-intensity interval training for heart failure with preserved ejection fraction: A protocol for systematic review and meta-analysis. Issue 27 (2nd July 2020) - Zhang, Sisi; Zhang, Jingxian; Liang, Congying; Li, Xiaochuan; Meng, Xiaoping
Abstract: Background: The benefits of high-intensity interval training (HIIT) are well-known, there is insufficient evidence about the effects of HIIT on heart failure with preserved ejection fraction (HFpEF). Method: Multiple databases include MEDLINE, PubMed, EMBASE, CINAHL, Web of Science, PEDro, Cochrane Library, and Google Scholar are used to search for randomized controlled trials investigating the effects of HIIT on HFpEF. All related articles published with the English language with no time limitation will be included. Two reviews independently conducted the selection, data extraction, and quality assessment. The primary outcome is exercise capacity. The secondary outcomes include quality of life (QoL), blood pressure (BP), ventricular function, and left ventricular diastolic function, symptom improvement, endothelial function, and arterial stiffness. Data analysis is performed with Review Manager Software (Version 5.3). Result: This systematic review and meta-analysis aim to evaluate the efficacy of HIIT on HFpEF, its outcome will provide reliable evidence for future studies. Conclusion: The findings of this study will be published in a related peer-reviewed journal. Registration number: INPLASY202050097